Intestinal Microbiota and Rheumatoid Arthritis: From Pathogenesis to Potential Therapies - Zawada, Wiktoria; Tartas, Iga; Kaczmarek, Krystian; Leszczyńska, Zofia Jadwiga; Romaniuk, Vladyslav; Szuleta, Urszula; Benecka, Agnieszka; Pietrończyk, Jakub; Benecka, Alicja; Wieczorek, Zuzanna; Prankiewicz, Natalia (Quality in Sport, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by progressive joint inflammation and multifactoral pathogenesis. Growing evidence indicates that the intestinal microbiota plays significant role in disease development and progression. Gut microbiota contributes to immune homeostasis, while dysbiosis-defined as altered microbial composition is associated with reduced diversity,expansion of pro-inflammatory taxa such as Prevotella copri and depletion of beneficial commensals. This review summarizes key mechanisms linking gut microbiota with RA, including increased intestinal permeability, immune dysregulation with Th17/Treg imbalance, molecular mimicry and altered production of microbial metabolites, particularly short-chain fatty acids. These processes are integrated within the concept of the gut-joint axis, explaining how intestinal disturbances may contribute to systemic and synovial inflammation. The potential of microbiota-derived biomarkers for diagnosis, prognosis and treatment response is also discussed. Additionally, emerging therapeutic strategies targeting gut microbiota, such as dietary interventions, probiotics and fecal microbiota transplantation are reviewed. Although promising, these approaches require further validation before clinical application.